2022
DOI: 10.3390/s22197417
|View full text |Cite
|
Sign up to set email alerts
|

Data Fusion-Based Musculoskeletal Synergies in the Grasping Hand

Abstract: The hypothesis that the central nervous system (CNS) makes use of synergies or movement primitives in achieving simple to complex movements has inspired the investigation of different types of synergies. Kinematic and muscle synergies have been extensively studied in the literature, but only a few studies have compared and combined both types of synergies during the control and coordination of the human hand. In this paper, synergies were extracted first independently (called kinematic and muscle synergies) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Leveraging the insights from our previous works ( Olikkal et al, 2022a , b ) it was observed that time-variant synergy models yielded best results, hence for this study, we opted for the time-variant synergy model. In case of time-variant models, a time-varying pattern is produced by combining synergies with time-varying scaling coefficients.…”
Section: Derivation Of Synergies In the Offline Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Leveraging the insights from our previous works ( Olikkal et al, 2022a , b ) it was observed that time-variant synergy models yielded best results, hence for this study, we opted for the time-variant synergy model. In case of time-variant models, a time-varying pattern is produced by combining synergies with time-varying scaling coefficients.…”
Section: Derivation Of Synergies In the Offline Modelmentioning
confidence: 99%
“…Principal component analysis (PCA) was applied on the cascaded velocity matrix to derive PCs that capture the maximum variance. Following our prior works ( Olikkal et al, 2022a , b ), to identify the optimal number of PCs, we selected those PCs the accounted for 0.98 (98%) of total variance using the Eq. (3) expressed as…”
Section: Derivation Of Synergies In the Offline Modelmentioning
confidence: 99%
See 2 more Smart Citations